Nilai Budaya Manugal bagi Pembentukan Karakter dalam Melestarikan Kearifan Lokal Masyarakat Suku Dayak Ngaju di Kalimantan Tengah - Timotius Dehen L. Djungan (Proceedings Series on Physical & Formal Sciences, 2021)
The traditional manugal culture (growing rice) is still carried out by the indigenous Ngaju tribe in Central Kalimantan. In manugal there is a division of labor between men, mothers and children. The manual farming method cannot be separated from the system of burning land which makes it unfriendly to the environment and is being abandoned by indigenous peoples. In fact, manugal can be used as an environmentally friendly way of farming by reusing land that has been burned, plowing the soil again and applying organic fertilizer, manure and chemical fertilizers. Apart from that, in human culture there are values that must be maintained because these values shape the character of children to be responsible and help others. These values include the value of handep hapakat (mutual cooperation), the value of patience, the spiritual value between nature, humans and God.